A new species of Waoraniella (Psocodea: ’Psocoptera’: Lachesillidae: Eolachesillinae) from the Reserva Florestal Ducke, Amazonas, Brazil - García Aldrete, Alfonso N.; Mockford, Edward L. (Instituto de Ecología, A.C., 2011)
Waoraniella vidali n. sp., the second species in the genus, is described and illustrated on the basis of a male from Amazonas, Brazil. The hypandrium and clunium are autapomorphic for the family. The phallosome is similar to that of Eolachesilla, and the character state Forewing Rs-M joined by a crossvein is found to appear in three genera of the subfamily Lachesillinae. Thus Waoraniella and Eolachesilla are close, and the genera of Graphocaeciliini stand apart in the subfamily.